Effect of HF Wave Frequency on N-atom Production in N\(_2\) HF Plasmas and Its Application in CN Thin Films Deposition - André Ricard; Mohammed Chaker; Malek Tabbal (Plasmas Afterglows with N2 for Surface Treatments synthesis 2024, 2025)
Microwave plasmas are produced in many chapters by launchers named Surfatron at 2450 MHz to form so-called Surface Wave (SW) plasmas. Another plasma RF (13.56 MHz) structure was compared to Surfatron launchers with application to TiO2 nitriding. Variations of N atom density have been measured by emission spectroscopy, calibrated using NO titration, in the N2 late and pink flowing afterglows as a function of the wave frequency f used to generate Surface Wave (SW) plasma. It is found that [N] increases with the absorbed power PA but saturates above a threshold power which decreases with f. At 2450 MHz and a constant pressure of 4 Torr, [N] reaches 1.5 x 1015 cm -3 in the saturation regime while a saturated value of only 7 x10 14 cm -3 is attained at 13.56 MHz. The density variations of [N] as a function of f and PA correlate in the increasing region with that of the vibrational temperature as a result of electron collisions and in the saturated region with the gas temperature when it exceeds 500-600 K. Finally, [N] increases with pressure from 2 to 8 Torr (at constant PA of 100 W) and decreases with the tube diameter (6 to 15 mm), at constant pressure of 4 Torr. These results show that the highest N-atom density is obtained at 2450 MHz. A source of N-atoms produced by such N2 afterglows was combined with laser ablation of graphite for CNX thin film deposition. The XPS and IR analysis of the films have shown that the presence of nitrogen atoms in the post-discharge enhances the incorporation of N into the CNx layers. The N incorporation increases as pressure is increased through the formation of hydrogenated carbon nitride groups while at low pressure of about 10-3Torr, unhydrogenated sp2 and sp3 CN bonds are produced in amorphous forms. The study concluded that the highest [N] value was obtained at 2450 MHz and that the power efficiency was also the highest at this same frequency.